(untitled) (FAVE Sección Ciencias Veterinarias, 2019)
Reading job applications sent to any company and, particularly, those related to the Veterinary profession, it becomes clear that, apart from the required specific technical and scientific expertise, applicants should also have a proactive spirit, leadership abilities and the capacity to work in a team, among other important social skills. Nowadays, it’s not enough having "wise" knowledge or "technical" expertise. Subjects should also have the ability to communicate effectively, demonstrate they can rely upon themselves and others, be sympathetic and empathetic and capable of integrating successfully in new work teams. In the official syllabus of the Veterinary Medicine career in Argentina, the ability to work in teams is not part of the specific content that the students have to learn. The Directed Studies Groups (DSG), are groups of students of different levels of the graduate course, that motivated by a common topic embark on tasks to deepen their knowledge on specific subjects, including research and / or extension. For them, learning to work in a team means learning to communicate effectively, to be supportive, to commit to the achievement of common goals, skills that should not be neglected and that are fundamental to speak of a professional with a comprehensive education.